**Answer** by matt
·
Feb 05, 2014 at 11:59 PM

You can use TeX notation. Here are several examples:

` $$ ax^2 + bx + c = 0 $$`

$$ ax^2 + bx + c = 0$$

` \( x = {-b \pm \sqrt{b^2-4ac} \over 2a}. \) `

\( x = {-b \pm \sqrt{b^2-4ac} \over 2a}. \)

` When $$a \ne 0$$, there are two solutions to \(ax^2 + bx + c = 0\) and they are $$x = {-b \pm \sqrt{b^2-4ac} \over 2a}.$$ `

When $$a \ne 0$$, there are two solutions to \(ax^2 + bx + c = 0\) and they are $$ x = {-b \pm \sqrt{b^2-4ac} \over 2a} $$

Copyright © 2010-16 DZone, Inc. - All rights reserved.